Childhood allostatic load predicts cardiometabolic health in adulthood - Elena Hinz; Alexander J. Vitali; Guangyu Tong; Herman Pontzer; William E. Copeland (Proceedings of the National Academy of Sciences, 2025)
Allostatic load (AL) measures multisystem physiological functioning to reflect the cumulative burden of chronic stress. Incurring AL during sensitive developmental periods such as childhood may affect health outcomes later in life, but longitudinal measures to test these life course effects are lacking. This study tested associations between childhood AL and adult cardiometabolic health in a large sample of youth repeatedly measured across ages 9 to 16, and their adult cardiometabolic health at age 30. AL scores were calculated at each age by summing across sex- and age-standardized values for biomarkers representing immune (C-Reactive Protein, Epstein–Barr Virus antibodies), neuroendocrine (cortisol, DHEA-s), and cardiometabolic indicators (body mass index; BMI). Adult cardiometabolic health was measured using a composite sum score of sex-standardized systolic and diastolic blood pressure, BMI, and waist-to-hip ratio. Multiple approaches aggregating repeated AL scores were tested, including mean, maximum, oldest available AL score across childhood, and a version omitting BMI from the index. Childhood AL was significantly associated with adult cardiometabolic health ( P < 0.001), with higher AL predicting worse cardiometabolic outcomes at age 30 in all models, regardless of how AL was defined. Sensitivity analyses to address potential bias from missing observations using 20 imputed datasets were consistent with unimputed models. Follow-up analyses suggested risk for adult cardiometabolic outcomes was primarily associated with C-reactive protein, DHEA-s, and childhood BMI. In this cohort study, physiological dysregulation experienced in early life had lasting consequences. These results underscore the importance of childhood as a sensitive period during which cumulative stress exposure can shape long-term health trajectories.